2018
DOI: 10.1093/bib/bby085
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of supervised methods for identifying differentially methylated regions in Illumina methylation arrays

Abstract: Epigenome-wide association studies (EWASs) have become increasingly popular for studying DNA methylation (DNAm) variations in complex diseases. The Illumina methylation arrays provide an economical, high-throughput and comprehensive platform for measuring methylation status in EWASs. A number of software tools have been developed for identifying disease-associated differentially methylated regions (DMRs) in the epigenome. However, in practice, we found these tools typically had multiple parameter settings that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 42 publications
3
72
0
Order By: Relevance
“…The following Comb-p parameters were used: seed p-value = 0.001, maximum distance between probes = 500 bp, and a minimum of three probes allowed in a DMR. This set of parameters is consistent with previous work 42 in the field and recommendations from simulation experiments 43 .…”
Section: Differentially Methylated Region Analysissupporting
confidence: 90%
“…The following Comb-p parameters were used: seed p-value = 0.001, maximum distance between probes = 500 bp, and a minimum of three probes allowed in a DMR. This set of parameters is consistent with previous work 42 in the field and recommendations from simulation experiments 43 .…”
Section: Differentially Methylated Region Analysissupporting
confidence: 90%
“…Interestingly, in a recent study, it has been observed that contiguous regions exist in the epigenome denoted as differentially methylated regions (DMRs) which are significantly associated with the various diseases [30], [31]. In addition, We found the comparative study of various DMR finding methods in [32] that might motivate us to extend our future work.…”
Section: Resultsmentioning
confidence: 83%
“…A recent study states that the epigenome contains contiguous regions denoted as differentially methylated regions (DMRs) that are significantly associated with numerous diseases [30], [31]. Mallik et al [32] conducted a comparative study of different DMR-finding methods; the results of this study might motivate our future work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One such challenge with supervised DMR-identification methods is their lack of power when the difference in beta values between two groups was small but consistent (i.e. difference in mean beta values is less than 0.05) (25). This is likely because supervised methods scan the genome to identify regions with adjacent low p-values, so a number of positions that pass a multiple-comparison-corrected significance threshold are required.…”
Section: Discussionmentioning
confidence: 99%
“…A number of statistical methods for identifying DMRs have been proposed (10,11,(17)(18)(19)(20), reviewed (21,22), and compared (23)(24)(25). Methods for DMR identification can be classified into supervised and unsupervised methods.…”
Section: Introductionmentioning
confidence: 99%